Estudo de operações lógicas através da modulação por posição de pulso no domínio da frequência (PPFDM) em AOTF convencional e baseado em fibra de cristal fotônico - Oliveira, Marcus Vinicius Nunes de (2014)
We propose a new method of optical modulation using a conventional Acousto-Optic Tunable Filter (AOTF) and an Acoustic Optic Tunable Polarization Filter (AOTPF) based on Photonic Crystal Fiber (PCF). In both devices the all-optical logic gates, namely AND and OR, are obtained by simultaneously operation of Optical Double Sideband (ODSB) modulation and a Pulse Position Frequency Domain Modulation (PPFDM). These devices shall operate with ultrashort soliton light pulses 100 ps and 55.5 fs for conventional AOTF and all-fiber AOTPF based on PCF, respectively. In this way, a pulse will carry two bits of information after been encoded by the modulation proposed here. We then analyze the modulation ODSB - PPFDM for input pulses, polarized in the two input modes, allowing a variation in the modulation parameter εcod for each input pulse. For conventional AOTF, a phase difference dfi = pi rad was considered between both input pulses, obtaining various values of the coding parameter offset |εcod| where the AND and OR logic operations were possible. For the all-fiber AOTPF based on PCF, a phase difference of dfi = 1,28pi rad was necessary between both input pulses to generate values of coding parameter offset |εcod|, for which AND and OR logic operations were possible.